2007
DOI: 10.1099/ijs.0.65109-0
|View full text |Cite
|
Sign up to set email alerts
|

Enterococcus camelliae sp. nov., isolated from fermented tea leaves in Thailand

Abstract: A Gram-positive and catalase-negative coccus that formed chains, strain FP15-1 T , isolated from fermented tea leaves ('miang'), was studied systematically. The strain was facultatively anaerobic and produced L-lactic acid from glucose. Demethylmenaquinone (DMK-7) was the major menaquinone. Straight-chain unsaturated fatty acids C 16 : 1 and C 18 : 1 were the dominant components. The DNA G+C content was 37.8 mol%. On the basis of 16S rRNA and RNA polymerase a subunit (rpoA) gene sequence analysis, strain FP15-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…Like in other fermented foods, the key microorganisms which play an important role in Miang fermentation are lactic acid bacteria [11][12][13]. In the last two decades, Lactobacillus pentosus, Lactobacillus vaccinostercus, Enterococcus casseliflavus, Enterococcus calmelliae, Lactobacillus thailandensis, Lactobacillus camelliae and Pediococcus siamensis have been reported to be involved in Miang fermentation [14,15]. Chaikaew et al [16] also reported that L. plantarum group was considered to be the predominant lactic acid bacteria in Miang.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Like in other fermented foods, the key microorganisms which play an important role in Miang fermentation are lactic acid bacteria [11][12][13]. In the last two decades, Lactobacillus pentosus, Lactobacillus vaccinostercus, Enterococcus casseliflavus, Enterococcus calmelliae, Lactobacillus thailandensis, Lactobacillus camelliae and Pediococcus siamensis have been reported to be involved in Miang fermentation [14,15]. Chaikaew et al [16] also reported that L. plantarum group was considered to be the predominant lactic acid bacteria in Miang.…”
Section: Introductionmentioning
confidence: 99%
“…Since tea leaves contain significant amounts of phenolic compounds, especially tannins that are known to be microbial growth inhibitors, the ability of microorganisms associated with the tea leaves fermentation to survive under tannin-rich conditions are of interest [17]. Many studies have evaluated tannin-tolerant lactic acid bacteria that have been isolated from Miang [11,[14][15][16]. Chaikaew et al [16] also confirmed that 23 isolates from 311 lactic acid bacterial strains isolated from Miang samples belonged to L. pentosus and exhibited high tannin-tolerant capabilities in medium containing 2.5% (w/v) tannins.…”
Section: Introductionmentioning
confidence: 99%
“…These bacteria are widely distributed in a variety of environmental habitats, even when there is little or no input from human and/or animal fecal sources (Byappanahalli et al, 2012). In addition, they are considered as lactic acid bacteria found in traditional fermented foods and in the dairy products (Sukontasing et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…nov. sp. et al (Okada et al 1986;Tanasupawat and Komagata 1995;Sukontasing et al 2007;Tanasupawat et al 2007;Klayraung and Okonogi 2009;Klayraung;and Okonogi 2009). The reason for this difference may be that the salt was added into pickled tea fermentation, and Miang tea is a non-salt fermented product (Okada et al 1986).…”
Section: Discussionmentioning
confidence: 99%
“…There are many reports on microbial fermented tea, but almost concentrated on the fermentation technology, health function and chemical components as well as isolation and identification of microbial strains (Okada et al 1986;Tanasupawat and Komagata 1995;Mo et al 2005;Jayabalan et al 2007;Sukontasing et al 2007;Tanasupawat et al 2007;Abe et al 2008;Jayabalan et al 2008;Mo et al 2008;Klayraung and Okonogi 2009;Klayraung;and Okonogi 2009; Highlights -The microbial species of pickled tea were much simple. -Lactobacillus plantarum is the dominant specie in pickled tea fermentation.…”
Section: Introductionmentioning
confidence: 99%